2005
DOI: 10.1097/01.smj.0000168701.08879.3f
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Cardiovascular Toxicity

Abstract: Cocaine abuse kills thousands every year. Preexisting coronary artery disease appears to account for many of the deaths, but often the mechanism is much more complex. There exists a widely held but utterly mistaken notion that cocaine-related deaths are due to drug overdose. Except in the case of drug couriers ("body packers") with massive drug exposure, death is not dose related, and cocaine blood levels cannot be used to predict toxicity. Most deaths occur after prolonged drug use, which initiates a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 43 publications
2
64
0
7
Order By: Relevance
“…Cocaine can be a cardiac depressant as well, with either direct or barorefl ex-mediated inhibition of sympathetic neural tonus from the CNS and sympathetic ganglia [14]. Although chronic use of cocaine can produce cardiac alterations that favor sudden death such as myocardial hypertrophy, fi brosis, and microvascular disease [15], these were not prominent in our cohort of decedents. With the enhanced cardiac risk caused by cocaine, capsaicin can exert synergistic untoward cardiac effects [16].…”
Section: Discussionmentioning
confidence: 95%
“…Cocaine can be a cardiac depressant as well, with either direct or barorefl ex-mediated inhibition of sympathetic neural tonus from the CNS and sympathetic ganglia [14]. Although chronic use of cocaine can produce cardiac alterations that favor sudden death such as myocardial hypertrophy, fi brosis, and microvascular disease [15], these were not prominent in our cohort of decedents. With the enhanced cardiac risk caused by cocaine, capsaicin can exert synergistic untoward cardiac effects [16].…”
Section: Discussionmentioning
confidence: 95%
“…Symptoms and signs of cocaine intoxication include anxiety, diaphoresis, tachycardia, hypertension, hyperthermia, mydriasis, hallucinations, convulsions, and cardiovascular collapse. ED staff should be aware of the clinical signs of cocaine toxicity during follow-up (12).…”
Section: Discussionmentioning
confidence: 99%
“…The association of chronic cocaine use with heart pathology was elucidated previously (e.g., by Tazelaar et al, 56 Karch and Billingham, 57 and Karch and Stephens 58 ), and was recently reviewed by Karch. 59 Karch et al 60 found that long-term cocaine use was necessary for the development of cardiac alterations, and that isolated postmortem measurements of blood cocaine concentrations (which may be high in occasional recreational users) should not be used to assess toxicity. In addition, Karch and Wetli 61 stressed that myocardial fibrosis and hypertrophy are common in general; both may promote arrhythmic sudden death.…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%